2020
DOI: 10.1029/2020wr027482
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Unfrozen Water Content of Frozen Soil Based on the Absorption Effects of Clay Surfaces

Abstract:  The presence of unfrozen water is explained by surface effects, adsorption forces and the nature of the electrical double-layer solution.  The surface effects are defined as the combined actions of molecules and negative charges on the clay surface.  The residual unfrozen water is a stable adsorption-layer solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…The recently developed heat pulse method and its combination with time/frequency domain reflectometry method may provide a solution for this [15,[99][100][101]. Mechanisms for determining the magnitude of unfrozen soil water content in frozen soils are still not clear and models used to predict unfrozen water content or soil freezing/thawing characteristics are still at their infancy [84,102]. In addition, more studies are required to understand how unfrozen soil water content and the increased freeze-thaw cycles would affect microbial activity, carbon and nitrogen cycles and the associated greenhouse gas emission, thickness of active layers [103,104], and landscape change [62,[105][106][107] under climate change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently developed heat pulse method and its combination with time/frequency domain reflectometry method may provide a solution for this [15,[99][100][101]. Mechanisms for determining the magnitude of unfrozen soil water content in frozen soils are still not clear and models used to predict unfrozen water content or soil freezing/thawing characteristics are still at their infancy [84,102]. In addition, more studies are required to understand how unfrozen soil water content and the increased freeze-thaw cycles would affect microbial activity, carbon and nitrogen cycles and the associated greenhouse gas emission, thickness of active layers [103,104], and landscape change [62,[105][106][107] under climate change.…”
Section: Discussionmentioning
confidence: 99%
“…The papers of 143 [77], 54 [78], 57 [79], 105 [80], 129 [81], 152 [82], 247 [76], and 279 [83] incorporated effects of unfrozen soil water into heat transfer processes to better understand the characteristics of soil freezing and thawing processes and frozen soil permeability or infiltrability. However, the mechanisms defining the magnitude of unfrozen water content still remain unclear and more studies are required [84]. The left column is the year that corresponds to the node on the horizontal line.…”
Section: The Most Recognized Journalsmentioning
confidence: 99%
“…This effect contributes to the steepest part of the curve shown in figure 1 (Tian et al, 2014). As the curve flattens, the unfrozen water content is composed progressively of more adsorbed water (Tian et al, 2014) that is tightly bound to the soil particles, and depending on the soil type, may form a film that completely separates the ice in the pore space from the soil grains (Jin et al, 2020). Soils in which this liquid water film occurs are termed 'solid-liquid-solid' (SLS) soils and are predominantly clays, where soil particles often carry a negative electrical charge (Koopmans and Miller, 1966).…”
Section: Constructing An Sfccmentioning
confidence: 99%
“…Alternatively, 'solid-to-solid' (SS) soils have pore ice in contact with soil particles, such as occurs in sandy soils (Koopmans and Miller, 1966). The soil type (SLS or SS) defines the residual water content -the liquid water left that does not freeze (or freezes extremely slowly) -as temperature continues to decrease (Jin et al, 2020). For example, studies of clays have found substantial liquid water fractions on the order of 20 m 3 /m 3 at temperatures as low as -25 • C (Bittelli et al, 2004b;Kong et al, 2022).…”
Section: Constructing An Sfccmentioning
confidence: 99%
“…Early empirical observations of freezing point depression were provided by laboratory experiments reported by Koopmans and Miller (1966) and Williams (1970). Freezing point depression is understood to occur because, in any individual soil pore, the effects of solutes and the attractive forces generated with the soil solids (capillarity and adsorption forces, Jin et al., 2020) reduce the free energy of the liquid water, such that the temperature must be less than T0 for the phase transition to occur. Freezing point depression is therefore attributed to (a) capillarity and adsorption effects (hereafter capillary effects, Spaans & Baker, 1996; Williams & Smith, 1989, p. 5; Zhou et al., 2018), and (b) the presence of salts (Williams & Smith, 1989, p 5; Williams, 1970, p. 16; Williams, 1964; Watanabe & Mizoguchi, 2002).…”
Section: Introductionmentioning
confidence: 99%